The Effectiveness of Financial Support Mechanisms for Small Businesses and Startups - Bakoeva Gulbakhor (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This paper evaluates the effectiveness of various financial support mechanisms available to small businesses and startups, including government grants, credit guarantee schemes, microfinance, venture capital, and crowdfunding. Drawing on empirical evidence from a range of developing and advanced economies, the study examines how these instruments affect firm survival, growth, and job creation. The analysis highlights that while targeted and well‑designed support programs can significantly improve access to finance and firm outcomes, weaknesses in implementation, information asymmetries, and misaligned incentives often undermine their potential. Policy recommendations emphasize better targeting, complementary non‑financial support, and robust monitoring and evaluation frameworks.